Long Distance Marriage among Academic Lecturers: A Maqāṣid al-Sharī‘ah Analysis of Spousal Rights and Obligations - An Ainy Zulfa Sadati; Arifana Nur Kholiq; Muhammad Syarif Hidayat (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
The phenomenon of long-distance marriage (LDM) among academic faculty members is on the rise due to career mobility, further studies, and the demands of the higher education profession. However, previous research has primarily focused on psychological aspects, communication, or family resilience in general, while studies that specifically examine academic faculty members as a professional group characterized by high mobility through the perspective of maqāṣid al-syarī‘ah remain limited. This study addresses this gap by analyzing LDM practices among academic faculty through the fulfillment of spousal rights and obligations based on the principles of hifẓ al-dīn, hifẓ al-nafs, hifẓ al-‘aql, and hifẓ al-nasl. The study employs a qualitative approach with a descriptive-analytical field study design, utilizing in-depth interviews with faculty members engaged in LDM, documentation, and normative analysis grounded in maqāṣid al-syarī‘ah. The results indicate that the sustainability of LDM is not solely determined by physical proximity but by the couple’s ability to reconstruct the fulfillment of rights and obligations through communication, role distribution, career support, and religious commitment. . The main findings reveal the existence of adaptive qiwāmah, a pattern of household leadership that remains oriented toward sharia responsibilities but is implemented flexibly in accordance with the demands of an academic profession. These findings indicate a contextual reinterpretation of the obligations of husbands and wives without neglecting the primary objectives of sharia. The novelty of this research lies in the development of the concept of adaptive qiwāmah based on maqāṣid al-syarī‘ah as a framework for understanding professional Muslim families. This research has implications for strengthening contemporary family fiqh as well as the need for higher education policies that are more responsive to the balance between academic careers and family resilience.